Variação, mudança linguística e português do Brasil na grammatica portugueza: curso superior (1920 [1887]), de João Ribeiro (1860-1934) - Silva, Anderson Rany Cardoso da (2021)
This dissertation investigates, in a historiographical perspective, the approach to linguistic variation, linguistic change and Brazilian Portuguese in Grammatica Portugueza: Curso Superior (1920 [1887]), by João Ribeiro (1860-1934). We weave for this research some specific objectives: i) to investigate the explicit or underlying conceptions of linguistic variation and change present in the selected historiographical source; ii) to point out the author's positions, favorable or contrary, in relation to the linguistic themes under study in this dissertation; iii) to identify the phonetic/phonological, morphological and syntactic phenomena that the author uses to treat linguistic variation and change; iv) to analyze the speeches about the intellectual figure of João Ribeiro, fruits of the history of brazilian linguistics, and his relationship with Brazilian Portuguese, as well as identify the conceptions adopted by the grammarian about this variety of Portuguese; v) to examine the rhetorical movements linked to João Ribeiro's grammar, as well as to identify the influences received by the author for the production of his work. To achieve these objectives, the research seeks theoretical and methodological support in the Historiography of Linguistics (SWIGGERS, 2004, 2013, 2014; KOERNER, 2014; ALTMAN, 2009, 2012). This discipline describes and explains the evolutionary course of linguistic knowledge. The concerns of the area do not reside only in presenting history, but also in interpreting it. We support our analytical reflections in the category of layer analysis of linguistic knowledge, proposed by Swiggers (2004), which makes it possible to investigate, from a dynamic perspective, the development of grammatical studies. In this sense, we analyze the context in which grammar is inserted (contextual layer), grammatical concepts (theoretical layer), the conduct of grammatical work carried out by the grammarian (technical layer) and the example used in the sources (documental layer). When we analyzed the contextual layer of the work, we identify that João Ribeiro was constituted as a multiple figure by the strength of his intellectuality in the late 19th century and early 20th century, as well as by the fact that he based himself on numerous other texts and authors for the production of his grammar. Moreover, the analysis of this layer still gave us space to understand that João Ribeiro moves away from the defending figure of the Portuguese of Brazil, as it seems to signalize, in a general way, the history of grammar in Brazil. On the contrary, in this grammar, João Ribeiro reveals himself to be a grammarian who reduces Brazilian Portuguese to a set of condemnable "Brazilianisms". From the analysis of the theoretical layer, we realize that João Ribeiro conceptualizes several types of grammar (general/universal, particular, historical, comparative and descriptive) and adheres to the historical-comparative method and, perhaps for this reason, approaches linguistic variation through interdiction and through acceptance of linguistic change. Focusing on the technical layer, we observe that, despite recognizing the existence of a Brazilian Portuguese, João Ribeiro in fact treats it from an explicit judgment of negative value. Finally, with the analysis of the documental layer, we conclude that the grammarian, besides using examples created by him in the treatment of the language, makes use of an apparatus based on previous literary writing, constituted of authors of Portuguese literature belonging to different historical moments of Portuguese.